About Ivan Pereverzev’s «Patriotism» - Наумов, Сергій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Research aim is to comprehend and rethink the public views of the author of «The Short Rules of Russian Spelling» (1782) and «The Topographical Description of the Kharkov Vicegerency with a Historical Preface» (1788) Ivan Pereverzev represented in his historical works and in the historical science Research methodology. The article is based on the use of the modern nationological toolkit, especially the concept of «national projects» and mapping as a tool/marker of nation-building.Scientific novelty. For the first time the identity of I. Pereverzev became a subject of a special study. The efforts of numerous researchers of the second half of the XX – early XXIth century to present him as a person aspiring to Ukrainian patriotism or even as a forerunner of the Ukrainian «national project» have been critically reviewed.Conclusions. The brief analysis of the text of the «Topographical Description of Kharkiv Vicegerency» shows that the author’s genesis of the «Nation of Rusyns» was being built entirely on the basis of the Russian-Little Russian ideas, Ukrainian lands being treated as «primordially Russian» and their population as a part of a single «Slavic-Russian tribe» («the Russian people»), while the cultural features of the Little Russians being explained as a result of harmful foreign (primarily Polish) influences. I. Pereverzev did not position himself as a bearer of any Little Russian / Ukrainian identity, nor did he demonstrate a commitment to relevant values. It is concluded that all attempts to search for any non-Russian cultural identities of I. Pereverzev in his works and therefore to show their importance for the «Ukrainian project» are no more than groundless and unjustified speculations.